Methane concentration in water column and in pore water of a coastal lagoon (Cabiúnas lagoon, Macaé, RJ, Brazil) - Fonseca,André Luiz dos Santos (2004)
The aim of this study was to evaluate methane concentration in water column and pore water at limnetic and littoral regions of a coastal lagoon. At the littoral region samples were taken from three monospecific macrophytes stands (Typha domingensis, Eleocharis interstincta and Potamogeton stenostachys). The methane concentration in the pore water at the littoral region was higher than the concentration found at the limnetic region in each fraction of the sediment. The higher methane concentration in the superficial fraction of the sediment (0-2 cm) was shown at the P. stenostachys stand (3.7 mM). It was the only significantly different (p<0.05) from the limnetic region. The pore water methane concentration increased with depth at the aquatic macrophytes stands. The methane concentration in the water column did not vary significantly among the sampling sites (p>0.05). It could be concluded that there was a high influence of aquatic macrophytes on the pore water methane concentration.